Stocking densities of juvenile Brycon orthotaenia: production parameters and economic benefits in net cages - Lago, Aline De Assis; Freitas, Rilke Tadeu Fonseca De; Pimenta, Maria Emília De Sousa Gomes; Mattos, Bruno Olivetti De; Reis Neto, Rafael Vilhena [UNESP]; Costa, Adriano Carvalho (Editora da Universidade Estadual de Maringá - EDUEM, 2014)
Developing a rearing technology requires the determination of the optimum stocking density. This study aimed to determine the best stocking density for Brycon orthotaenia juveniles grown in net cages, during the rearing phase. The research was conducted at the Experimental Farm of EPAMIG, in Felixlândia, Minas Gerais State, in the Três Marias Reservoir. 9,000 fingerlings were distributed into 12 net cages, 2 m³ each, according to a completely randomized design with three replications and four different stocking densities (150, 300, 450, 600 fish m-3). Random samples were taken from each net cage, at the onset of the experiment and at 60 rearing days, to assess production parameters, specific growth rate and uniformity. We verified a positive linear relationship (p < 0.05) for final biomass (r² = 0.88), weight gain (r² = 0.87), productivity (r² = 0.86), apparent feed conversion (r² = 0.96) and economic viability (r² = 0.96). For survival (r² = 0.98), the relationship was negative (p < 0.05). There were no significant differences between treatments (p > 0.05) for growth parameters, uniformity and final weight. It can be concluded that the density of 300 fish m-3 is the most suitable, because it provides higher net revenue, survival, and a good feed conversion.

Para o desenvolvimento de uma tecnologia de cultivo é necessária a determinação da densidade de estocagem ideal. Objetivou-se determinar a melhor densidade de estocagem para juvenis de Brycon orthotaenia, cultivados em tanques-rede, durante a fase de recria. A pesquisa foi conduzida na Fazenda Experimental da Epamig, em Felixlândia, Estado de Minas Gerais, na represa de Três Marias. Foram utilizados 9.000 alevinos, distribuídos em 12 berçários com 2 m³ em tanques-rede, seguindo o delineamento inteiramente casualizado, com três repetições e quatro diferentes densidades de estocagem (150, 300, 450, 600 peixes m-3). Amostras aleatórias de cada tanque-rede foram coletadas para as avaliações, no início do experimento e aos 60 dias de cultivo. Foram estimados os parâmetros produtivos, índice de crescimento específico e uniformidade. Obteve-se uma relação linear positiva (p < 0,05) para biomassa final (r² = 0,88), ganho de peso da biomassa (r² = 0,87), produtividade (r² = 0,86), conversão alimentar aparente (r² = 0,96) e para viabilidade econômica (r² = 0,96). Para sobrevivência (r² = 0,98), a relação linear foi negativa (p < 0,05). Não houve diferença significativa entre os tratamentos (p > 0,05) para os parâmetros de crescimento, uniformidade e peso final. Conclui-se que a densidade de 300 peixes m-3 é a mais indicada, pois, proporciona maior receita líquida, sobrevivência e boa conversão alimentar.
Densidades de estocagem de juvenis de Brycon orthotaenia: parâmetros produtivos e benefícios econômicos em tanques-rede
Keywords: aquaculture; intensive system; survival; profitability; São Francisco river; aquicultura; sistema intensivo; sobrevivência; rentabilidade; rio São Francisco